Gendered Dimensions of AI Integration in Language Learning: A Review in the Context of Art and Digitalization - Alireza Dezfooli (Asparkía)
This review examines the integration of artificial intelligence (AI) in education, particularly its impact on language learning and gender perceptions. It examines AI’s transformative potential in enhancing educational outcomes and addresses gender biases in AI interactions. Emphasizing the importance of ethical AI practices, the study highlights the need for a nuanced understanding of how gender influences interactions with AI systems in educational contexts. By exploring these dynamics, it sheds light on the complexities of technology adoption and its implications for gender equity in education.